A Semantic Web Approach to Low-Level Features in Images - Alves, Miguel Bento; Damásio, Carlos Viegas; Correia, Nuno (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
We present a Semantic Web based approach that meets the requirements for images retrieval based on low-level features. For that, we developed a prototypical implementation using a Semantic Web framework, linking open data ontologies and image processing libraries. We created an ontology to support the low-level features data of images. Furthermore, we created semantic rules to define concepts based on lowlevel features. We show how the different mechanisms of the Semantic Web may help multimedia management, both for storage and in retrieval tasks.